2010
DOI: 10.1107/s1744309110046208
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of an apo form of human arginase: using all the tools in the toolbox simultaneously

Abstract: Arginase (EC 3.5.3.1) is an aminohydrolase that acts on l-arginine to produce urea and ornithine. Two isotypes of the enzyme are found in humans. Type I is predominantly produced in the liver and is a homotrimer of 35 kDa subunits. Human arginase (hArginase) I is seen to be up-regulated in many diseases and is a potential therapeutic target for many diverse indications. Previous reports of crystallization and structure determination of hArginase have always included inhibitors of the enzyme: here, the first ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Our experiments demonstrated that the cross-linked seeds retained their capacity to induce crystal formation. This has also been confirmed by Newman et al (2011) in work on human arginase.…”
Section: Cross-linking Of Seedssupporting
confidence: 61%
See 1 more Smart Citation
“…Our experiments demonstrated that the cross-linked seeds retained their capacity to induce crystal formation. This has also been confirmed by Newman et al (2011) in work on human arginase.…”
Section: Cross-linking Of Seedssupporting
confidence: 61%
“…Since the introduction of MMS in 2004, a number of reports (Obmolova et al, 2010;Persson et al, 2010;Newman et al, 2011) have confirmed that it is a viable optimization alternative. It can produce high-quality crystals from poor starting points that are not amenable to the classical optimization strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Although we selected only one of the crystal forms as seed stock, we found that both forms could be obtained from the same seeds (Figure 1A-a and C-c). Similar results have been obtained recently with human arginase, 18 but since we have not yet characterized those crystals by X-ray diffraction, we will not discuss this observation further. Crystal Growth & Design…”
Section: Ribonuclease Asupporting
confidence: 72%
“…Using the PILs in conjunction with sparse matrix screens, such as the JCSG+ screen used in this study, increases the likelihood of identifying crystallization conditions which can be further optimized. This is a methodology which we are actively applying to the crystallization of proteins which are difficult to crystallize; these PILs have already been shown to be useful in our lab in generating crystals of diffraction quality for a difficult project …”
Section: Discussionmentioning
confidence: 99%